Forehead against Resistance (FAR): Preliminary Findings from A Clinical Alternative to Shaker’s Type of Exercise - Radish Kumar Balasubramaniam; Rahul Krishnamurthy; Athira Rajan; Suprasanna K (Gastroenterology Research and Practice)
Background. Reduced UES opening is a well-known risk factor for dysphagia. The Shaker exercise and the CTAR are the widely used intervention strategies to bring about effective UES opening. But there are well-known difficulties with the clinical use of these two exercise regimes. The present study proposes a clinical alternative to Shaker’s exercise and CTAR called the forehead against resistance (FAR) and its variants without altering the central principles of these two regimes. The aim of the present study was to investigate the efficacy of FAR and its variants in bringing about UES opening. Method. The study used a comparative cross-sectional study design, with the nonrandomized convenient sampling that included 27 healthy adults. MBS was carried out in the anterior-posterior and lateral views, while the participants performed FAR and its variants. The UES diameter was measured in the baseline and with the subjects performing FAR maneuver and its variants. Results. The result revealed that the participants had greater UES opening on FAR and its variant than the baseline swallow. Also, mean values of UES opening were greater for FAR with chin tuck when compared to FAR alone, although there was no significant main effect with exercise. Conclusion. FAR and its variant could be one of the options for increasing UES opening in individuals with dysphagia.